Selective disordering of lamella-forming diblock copolymers under an electric field - Sevink, G. J. A.; Pinna, M.; Langner, K. M.; Zvelindovsky, A. V. (Soft matter, 2011)
Self-assembled block polymers show great potential to serve as templates for the fabrication of nanoscale structures for devices, provided that structural features such as defects and global orientation can be fully and efficiently controlled. The most efficient way to control these features is by application of an electric field, to orient features parallel to the electric field. Several aspects of the thermodynamic and kinetic factors that determine the reorientation dynamics have been studied in recent years and are increasingly understood. Current experiments focus on reorientation close to the order-disorder transition (ODT) temperature, where an efficient mechanism involving selective disordering is long anticipated but subject to lively debate. Here, we complement the increasing experimental understanding by a detailed and unifying computational analysis of all distinct microscopic stages in this new reorientation mechanism. The unification step originates from the comparison of two different models, one based on a molecular description and the other phenomenological. The results have a general character and may also serve as a stepping stone for understanding microscopic response pathways due to other kinds of deformation, such as mechanical stress or shear. We find that reorientation is most effective for temperatures that are slightly below ODT, at which the system is slightly demixed and the balance between surface tension and the ponderomotive force is optimal.